Whole-exome sequencing reveals candidate high-risk susceptibility genes for endometriosis - Susanna Nousiainen; Outi Kuismin; Siiri Reinikka; Roosa Manninen; Sara Khamaiseh; Mari Kuivalainen; Anna Terho; Sari Koivurova; Maarit Niinimäki; Kari Salokas; Markku Varjosalo; Anne Ahtikoski; et al. (Human Genomics, 2023)
Abstract Background Endometriosis is a common, chronic disease among fertile-aged women. Disease course may be highly invasive, requiring extensive surgery. The etiology of endometriosis remains elusive, though a high level of heritability is well established. Several low-penetrance predisposing loci have been identified, but high-risk susceptibility remains undetermined. Endometriosis is known to increase the risk of epithelial ovarian cancers, especially of endometrioid and clear cell types. Here, we have analyzed a Finnish family where four women have been diagnosed with surgically verified, severely symptomatic endometriosis and two of the patients also with high-grade serous carcinoma. Results Whole-exome sequencing revealed three rare candidate predisposing variants segregating with endometriosis. The variants were c.1238C>T, p.(Pro413Leu) in FGFR4, c.5065C>T, p.(Arg1689Trp) in NALCN, and c.2086G>A, p.(Val696Met) in NAV2. The only variant predicted deleterious by in silico tools was the one in FGFR4. Further screening of the variants in 92 Finnish endometriosis and in 19 endometriosis–ovarian cancer patients did not reveal additional carriers. Histopathology, positive p53 immunostaining, and genetic analysis supported the high-grade serous subtype of the two tumors in the family. Conclusions Here, we provide FGFR4, NALCN, and NAV2 as novel high-risk candidate genes for familial endometriosis. Our results also support the association of endometriosis with high-grade serous carcinoma. Further studies are required to validate the findings and to reveal the exact pathogenesis mechanisms of endometriosis. Elucidating the genetic background of endometriosis defines the etiology of the disease and provides opportunities for expedited diagnostics and personalized treatments.